A Longitudinal Study of Microfinance and Poverty Reduction in Nigeria - Adesina, Tolulope Femi; Makinde, Damilola Ayomiposi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study investigated the impact of microfinance banks on poverty reduction in Nigeria, with a specific focus on their contributions to financial inclusion and economic empowerment. Despite numerous government-led poverty alleviation initiatives, poverty remains widespread, highlighting the need to explore alternative and sustainable approaches. Drawing on secondary data from the Central Bank of Nigeria and the National Bureau of Statistics, the research applies econometric methods to evaluate the relationship between microfinance operations and key poverty indicators. The findings reveal that microfinance banks play a significant role in reducing poverty by improving access to credit and supporting small-scale enterprises. The study recommends strengthening microfinance institutions through targeted policy interventions to enhance their long-term impact on poverty alleviation.